Pengaruh Dimensi Kualitas Pelayanan dan Kepuasan Terhadap Loyalitas Pelanggan - Vivi Ristanti; Muchsin Saggaff Shihab; Endi Rekarti (Program Studi Magister Manajemen FE Unsri, 2011)
This research examines the effect of service quality, customer satisfaction and customer loyalty. This Research is quantitative and explanative in nature. The five dimensions of SERVQUAL of Parasuraman’ concepts which include tangibility, reliability, responsiveness, assurance and empathy were employed. Both primary and secondary data were obtained. Secondary data were obtained from various sources such as journal, and books. Primary data were obtained by using questionnaire. Using accidental sampling technique, a total of 88 responses were obtained. Data were examined using both descriptive and statistical analysis. Using path analysis, it was found that empathy had influence on satisfaction and loyalty. Furthermore, guarantee and satisfaction had influence on loyalty.Keywords: quality, satisfaction, loyalty, SERVQUAL